Effect of Helicobacter Pylori Infection on Nutritional Status in Polish Teenagers - Anna Szaflarska-Popławska; Anetta Soroczyńska-Wrzyszcz (Gastroenterology Research and Practice)
Purpose. Data on an association between Helicobacter pylori (H. pylori) and nutritional status in children are conflicting. We designed a large-sampled prospective community-based study to examine the differences in average body indices among Polish teenagers depending on their H. pylori status. Methods. From September 2008 to June 2015, 3067 second junior high school students aged between 13 and 17 years (mean age: 14.5) from 11 randomly selected schools from Grudziadz, Poland, were recruited. For the cohort, 13C urea breath test for current H. pylori infection was performed and data on anthropometric measurements and sociodemographic characteristics were collected. Z scores of height for age (HAZ), weight for age (WAZ), and BMI for age (BMIZ) were calculated. Results. The H. pylori colonisation rate was 23.6% with no gender difference. Compared to noninfected, H. pylori infected had significantly lower mean WAZ (0.0085) and BMIZ scores (p=0.0246). Univariate linear regression models showed that living in the old town district and consumption of tap water were negative predictors of HAZ, living in the old town district, using collective catering facilities, and H. pylori infection were negative predictors of WAZ, and using collective catering facilities and H. pylori infection were negative predictors of BMIZ. In the multiple regression analyses, living in the old town district (p=0.0039), using collective catering facilities (p<0.0001), and H. pylori infection (p=0.0269) were confirmed to be independently associated with lower WAZ, whereas using collective catering facilities (p<0.0001) and H. pylori infection (p=0.0265) were confirmed to be independently associated also with lower BMIZ. Conclusion. Our finding confirms the evidence on independent negative influence of H. pylori infection on nutritional status in Polish teenagers.